Studies of the Fecundity of Sind Sardine fish, Sardinella sindensis (Day, 1878) (Family: Clupeidaee), from Karachi Coast, Pakistan. - safi, Amtyaz; Hashmi, Usman; Khan, Atiqullah; Khan, Zaheer (International Journal of Biological Research, 2013)
Sardinella sindensis is one of the dominant small pelagic fish of Karachi coast of Pakistan. Investigation on fecundity of sind sardinella was studied from January 2001 to April 2002. A total of 37 ovaries were examined of stages IV-VI (when not running). Mean fecundity ranged from 47521 to 110876 eggs. Log-log relationship between fecundity with total body-length, fish-weight & ovary weight were correlated. Therefore it may be mentioned that the fecundity is generally proportional to the size of the ovary, which in turn is related to the size of the fish. The mean number of ova/g body weight and mean number of ova/g ovary weight were found to be 2425.250 and 9537.855 respectively. The gonads are two lobed; the left lobe is more fecund than the right one.